Sugar fermentation profiles of bifidobacteria from rat gut - Lijana FANEDL; Gorazd AVGUŠTIN (Acta Agriculturae Slovenica)
Sugar fermentation profiles of 21 bifidobacterial isolates from rat small intestine were analyzed using the API 50CH test. The isolates were pooled into three main groups on the basis of the fermentation of 49 sugars. The sugar fermentation profiles of main groups were different from those of known bacterial species from the genus Bifidobacterium. According to the calculated phenetic similarity values the three groups of gut isolates were quite distant to each other, too. The group A seemed to be quite different from all 13 tested bifidobacterial type strains, the group B seemed to be phenotipically similar to B. magnum, while the group C displayed the highest similarity to the B. infantis type strain. The isolate 69 appeared to be different from all other gut isolates and seemed to be related either to B. pseudolongum or B. coryneforme type strains. Although the bacterial strains could not be classified into phylogenetic taxonomy units according to the phenotypic characteristics, it seems that the isolated rat gut bifidobacterial strains belonged to so far unidentified species.